2005
DOI: 10.1074/jbc.m501847200
|View full text |Cite
|
Sign up to set email alerts
|

The Oligomeric T4 Primase Is the Functional Form duringReplication

Abstract: Replisome DNA primases are responsible for the synthesis of short RNA primers required for the initiation of repetitive Okazaki fragment synthesis on the lagging strand during DNA replication. In bacteriophage T4, the primase (gp61) interacts with the helicase (gp41) to form the primosome complex, an interaction that greatly stimulates the priming activity of gp61. Because gp41 is hexameric, a question arises as to whether gp61 also forms a hexameric structure during replication. Several results from this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 39 publications
0
31
0
1
Order By: Relevance
“…been shown to inhibit the activity of the entire primase oligomer (38). The results of this experiment indicate that the primase protein is much less processive in the presence of gp32-A than wt-gp32 (Table 1 and Fig.…”
Section: Figure 4 Priming Activity With Wt-gp32 and Gp32-a Proteinsmentioning
confidence: 63%
“…been shown to inhibit the activity of the entire primase oligomer (38). The results of this experiment indicate that the primase protein is much less processive in the presence of gp32-A than wt-gp32 (Table 1 and Fig.…”
Section: Figure 4 Priming Activity With Wt-gp32 and Gp32-a Proteinsmentioning
confidence: 63%
“…In early work gel shift and protein-protein chemical cross-linking methodologies had shown that the gp61 primase subunit binds to the gp41 helicase hexamer at an approximately 1∶6 subunit stoichiometry (5,7). In contrast, Benkovic and coworkers have interpreted more recent and indirect fluorescence anisotropy and scanning calorimetry experiments (10)(11)(12) to argue that the primase subunits may interact with gp41 in an approximately 6∶6 subunit stoichiometry. This difference is important because in a primosome containing one primase and six helicase subunits the primase must be shared, which makes very different functional and mechanistic demands on both helicase and primase mechanisms than does a 6∶6 ratio, as is found in the hexameric helicase of bacteriophage T7, where every helicase subunit carries its own primase domain (13).…”
mentioning
confidence: 99%
“…This assay makes possible the separation of binding and catalytic parameters and the study of real-time kinetics. It is based on steady-state fluorescence anisotropy (r), which is sensitive to rotational diffusion, and thus suitable for studies aiming to identify structural modifications leading to a significant change in molecular size (12)(13)(14)(15). Using a fluorescent probe covalently linked to the GT dinucleotide, this makes it possible to follow DNA binding and dinucleotide release, because both steps strongly influence molecular size of the fluorescent moiety.…”
mentioning
confidence: 99%